Os conceitos no tratamento da informação arquivística: Unidade basilar para a compreensão do conteúdo documental - Cervantes, Brígida Maria Nogueira [UNESP]; Kiyonaga, Cynthia Maria Suenaga [UNESP]; Rodrigues, Maria Rosemary (FapUNIFESP (SciELO), 2017)
The relevancy of Paul Otlet and consequently of Bibliography and Documentation in Information Science is emphasized on the Treaty of Documentation, that developed the content analysis of the documents through the extraction of representative terms which are currently related to concepts. The importance of identify concepts for intellectual treatment of information consolidate itself each day expanding its use to other fields, as it is identified by the approaching of Archival Science and Information Science by conducting studies on Subject Treatment of Information in archives and their application in archival environment. The objective of the present study was emphasizing the relation of bibliographical studies for the representation of concepts in intellectual treatment of information in the scope of Archival Science. The employed methodology was an exploratory research and its methodological proceeds consist in a bibliographical study. It was verified that activities involving intellectual treatment of information in Library Science and Archival Science are deliberated by Subject Treatment of Information. Insofar as they benefit by its theories and documental treatment proposals in order to retrieve information through identification and concepts representation, thus they are considered as knowledge units and base of Subject Treatment of Information. In It was also emphasized the importance of bibliographical studies during the development of Knowledge Organization and Representation, when Paul Otlet mentions that it is necessary identify concepts before convey an idea. Such perspective remains current and reinforce itself as it is demonstrated by the relation of classification concepts and description in Archival Science to the processes in Knowledge Organization and Representation.
Concepts in treatment of archival information: Basic unit for the comprehension of documentary content
Keywords: Bibliography; Concept; Documentation; Knowledge organization and representation; Subject treatment of information